We are sorry to inform the end of our activities: representations and practices of the organizational decline in video rental stores - Pinhal, Vanessa Alves; Ferreira, Daniel Victor de Sousa; Borges, Jacquelaine Florindo (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This article aims to analyze social representations and strategic practices of video rental store managers with respect to the micro/macro relational tensions that characterize the decline of such organizations. From a perspective that conceives of strategy as practice, the research was conducted within a qualitative approach. Concerning the data collection, interviews and a projective technique with video rental store owners were used. The content analysis was applied to deal with the relational tension results and the elements of human agency: iterative, projective, evaluative-practical. The results demonstrate that evaluative-practical managers make changes while seeking better results and are careful with challenges, whereas iterative managers continue to work as they always did, by serving a few loyal clients and being indifferent to adversity. In spite of different strategic practices, managers share an image in the projective dimension: the death of video rental stores. Thus, strategy as a social practice encompasses themes of organizational change and decline as (anticipated) experience of mourning in organizations.